1996
DOI: 10.1093/treephys/16.11-12.949
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nitrogen, phosphorus, and potassium uptake capacity and root growth in mature alternate-bearing pistachio (Pistacia vera) trees

Abstract: We examined interrelationships between crop load, nitrogen (N), phosphorus (P), and potassium (K) uptake, and root growth in mature, alternate-bearing pistachio (Pistacia vera L.) trees. Pistachio trees bear heavy (on-year) and light (off-year) fruit crops in alternate years. Uptake and partitioning of N, P, and K among tree parts were determined during (a) spring flush (mid-March to late May), (b) nut fill (late May to early September), and (c) postharvest-leaf senescence (late September to early December). N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 33 publications
4
46
0
1
Order By: Relevance
“…Nitrogen uptake by woody plants is reduced as vegetative growth or reproductive sink activity declines, and if uptake does occur N is preferentially allocated to roots and stored (Weinbaum et al 1978;Sanchez et al 1992;Rosecrance et al 1996;Quartieri et al 2002). In fact, pulse experiments with labeled N (with and without water) at the Owens and Mono Lake sites indicate that the N uptake capacity of all of our study species declines by over 80% from spring when growth rates are high to summer when growth slows (J.J. James and J.H.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen uptake by woody plants is reduced as vegetative growth or reproductive sink activity declines, and if uptake does occur N is preferentially allocated to roots and stored (Weinbaum et al 1978;Sanchez et al 1992;Rosecrance et al 1996;Quartieri et al 2002). In fact, pulse experiments with labeled N (with and without water) at the Owens and Mono Lake sites indicate that the N uptake capacity of all of our study species declines by over 80% from spring when growth rates are high to summer when growth slows (J.J. James and J.H.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium accumulation in annual organs during the nut fill period is five times greater in ON-than in OFF-years (Picchioni et al, 1997). Potassium uptake during the nut fill period is six-fold greater in ON-than in OFF-year trees and over 90% of the total annual K uptake occurs during the same period, with the majority of K accumulating in the fruit (Rosecrance et al, 1996). It has been reported that 70 mg kg − 1 NH 4 OAc-extractable K is probably sufficient for optimum seedling growth of pistachio (Tajabadi Pour et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Pistachio trees have a high K demand and the annual K removal by fruits and leaves approximates nitrogen removal (Rosecrance et al, 1996). Potassium accumulation in annual organs during the nut fill period is five times greater in ON-than in OFF-years (Picchioni et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…과실 의 무기영양분 중에서 질소 (N)와 칼륨 (K)의 비율이 특히 높 은데, 착과량이 많을수록 나무에서 흡수된 N과 K는 주로 과실 로 분배된다 (Choi et al, 2011;Hansen, 1980;Lenz, 2000;Rosecrance et al, 1996). 감나무에서 여름 N 공급량이 적을 때 착색과 당도는 증가하지만 과실 비대가 감소하고 꽃눈분 화가 나빠져 이듬해 착뢰수가 적어진다 (Choi et al, 2013a).…”
Section: 과수에서 착과량이 증가하면 무기영양분 요구량이 많아지는unclassified